E-Learning with an AI Learning Assistant for Legal Education in Public Administration - Wartenberg, Katrin (International Journal of Advanced Corporate Learning (iJAC), 2025)
This case study explores an innovative e-learning ecosystem for legal training in local government that integrates structured video lectures, interactive quizzes, and personalized microlearning powered by Micromate, an AI conversational learning assistant. Micromate complements complex legal topics—such as procurement law and housing benefit law—with accessible five-question chat-based microlearning sessions. The system uses generative AI to auto-create quiz sessions, analyzes individual forgetting curves, and adapts to each learner’s behavior. Five-question sessions fit seamlessly into daily routines, while gamification elements such as badges sustain motivation. Content is dynamically unlocked based on course progress, encouraging continuous engagement. Deployed across three pilot courses, Micromate achieved 70% voluntary participation among eligible staff, over 12,000 quiz questions answered during the six-month pilot phase across three e-learning-courses, and a 300% increase in weekly questions (800→2,400 from week 1 to 28). This comprehensive approach redefines professional development in public administration by creating efficient, engaging, and personalized learning experiences that enhance knowledge acquisition and retention